2020
DOI: 10.34197/ats-scholar.2019-0006oc
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Serious Illness Conversation Guide to Improve Communication with Surrogates of Critically Ill Patients. A Pilot Study

Abstract: Background : International family-centered critical care guidelines recommend formal, structured communication to ensure that clinical decision making is informed by a shared understanding of diagnosis and prognosis and patient goals and preferences. Tools to facilitate these recommendations are limited. Objective : To examine the feasibility, acceptability, and utility of a standardized serious illness conversation (SIC) to guide communication between nonpalliative care trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…It was suggested that relying solely on the SQ could overlook some patients who would benefit from a palliative approach [ 25 , 26 , 50 ]; similarly, replying ‘no’ to the SQ was not always thought to require a serious illness conversation [ 50 ]. Triggering criteria for a conversation did not guarantee that a conversation would be held, and without a structured tracking system it could be difficult for clinicians to know who had, or had not, completed serious illness conversations [ 35 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that relying solely on the SQ could overlook some patients who would benefit from a palliative approach [ 25 , 26 , 50 ]; similarly, replying ‘no’ to the SQ was not always thought to require a serious illness conversation [ 50 ]. Triggering criteria for a conversation did not guarantee that a conversation would be held, and without a structured tracking system it could be difficult for clinicians to know who had, or had not, completed serious illness conversations [ 35 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…= 83 (62 y) 41 (55%) 45 (54%) Intervention and control patients had similar end-of-life health care utilization as measured by the mean number of NQF-endorsed indicators. Pasricha et al (2020) [ 43 ] U.S. To examine the feasibility, acceptability, and utility of a standardized SIC to guide communication between nonpalliative care trained providers and surrogates of critically ill, mechanically ventilated patients. Mixed-methods quality improvement pilot study.…”
Section: Table A1mentioning
confidence: 99%
“…In 2018, the University of Pennsylvania Abramson Cancer Center implemented the Serious Illness Care Program (SICP) developed by Ariadne Labs, a communication intervention designed to enhance timing, frequency, and quality of shared patient-provider decision-making in oncology. 19,20 Oncology clinicians are encouraged to document SIC using an EHR module, which generates a semi-structured "Serious Illness Conversation" note with subheadings by SIC domain. Prior to this implementation, all clinicians at Abramson Cancer Center were instructed to use an "Ad- "She doesn't want to experience any you willing to go through for the Limited hospitalizations, some testing and treatments; major side effects unless there is a possibility of gaining more time?…”
Section: Dataset and Schemamentioning
confidence: 99%
“…We salute recent efforts by Parischa and colleagues to improve communications in critical illness ( 1 ). This remains an area of healthcare disparity.…”
mentioning
confidence: 95%